Influence of Encapsulated Nanodiamond Dispersion on P(3HB) Biocomposites Properties - Almeida Neto,Gabriel Rodrigues de (2017)
Studies regarding biodegradable nanocomposites to be used as orthopedics devices have been intensified. This work aims to investigate the influence of ND dispersion on thermal and mechanical properties of a biocomposite of poly(3-hydroxybutyrate) (P(3HB)) reinforced with nanodiamonds (ND) intended to be used as orthopedics devices, with advantages as biodegradability. In order to improve its dispersion, P(3HB) has encapsulated ND in three different mass ratios: P(3HB):ND(16:1), (12:1) and (8:1). However, for all formulations, NDs are presented as agglomerates, in different intensities. In order to relate the distribution of ND within the polymer matrix and biocomposite properties, TGA, DSC, and DMA analysis were done. The formulation with higher content of ND, P(3HB):ND(8:1), presents larger aggregates; thus, decreasing its properties. With smaller and more distributed agglomerates, the 12:1 ratio composite displayed superior storage modulus and glass transition temperature, probably due to better polymer chain restriction.